Leading Clarity - Deuster, Brad (Ascent Audio, 2019)
Leading Clarity offers a bold proposal that changes the trajectory of your business and leadership. Today's business environment is more complex than at any time in history with greater ambiguity, chaos, and uncertainty. Too often, individuals and organizations become bogged down with competing priorities and the constant press of daily demands. This tangled mass of noise effectively handicaps every facet of business. This book provides a proven, time-tested strategy that has brought dynamic results to hundreds of organizations of all scope and size. Leading Clarity takes you beyond understanding the strengths and weaknesses of individuals and teams, and guides you through a dynamic process that unveils what is most critical and most enduring about your business. Clarity is the key measure of unprecedented success and a vital factor in productivity, engagement, and performance. Now, Deutser is sharing the secrets of his proven blueprint for creating clarity. With these powerful principles and stories of how to put them to work, you too can leverage the exponential impact of clarity. Clarity is the dynamic force that aligns and connects the most critical business principles. Leading Clarity moves you beyond any preconceived limitations and sets new direction, expectation, and pathways for success.